Behavioral Characteristics of Individuals with Down Syndrome. Issue 3 (3rd July 2018) - Patel, Lina; Wolter-Warmerdam, Kristine; Leifer, Noel; Hickey, Francis
ABSTRACT: Introduction : Children and young adults with Down syndrome can demonstrate increased behavior problems compared to their typically developing peers through childhood and adolescence. Though current tools measure behavior problems in persons with intellectual disabilities, they do not capture all the behavioral problems that can occur in individuals with Down syndrome. We: (1) identify new behavioral problems observed by parents of persons with Down syndrome that are not included on standard measures of behavior, but observed by parents; (2) examine the degree to which these behaviors may be impacted by expressive language, gender, and age; and (3) suggest the need to create a new measure. Methods : This investigation examines the identified behaviors and level of parental concern of 274 children and young adults with Down syndrome receiving care at a single medical center. Results : Ninety-four percent of children with Down syndrome engaged in behavioral problems, which was significantly correlated with age and expressive language abilities. Conclusions : Early detection of problem behaviors provides an opportunity for parent resources and professional support to reduce long-term adverse effects and prevent the occurrence of additional problematic behaviors. Results from this study indicate that a measure to more effectively capture and differentiate problem behaviors in children and adolescents with Down syndrome is greatly needed.